قياس مقدرة الطلاب على التخرج في المدة المحددة في الكليات الهندسية (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Delayed graduation raises many questions about the ability of college students to graduate on time. Answering these questions leads to identifying the reasons that prevent this from being achieved, whether the study system is annual or semester. This research aims to achieve two goals, the first is to measure the ability of college students in engineering majors to finish their studies and graduate in the standard period of study. The second goal is to identify the most important reasons behind their inability to finish their studies in the standard period of study. The faculty of engineering at Misurata university has been chosen to be the subject of the study. In order to achieve the research goals, the method of measuring the ability of the process called Process Capability was adopted to determine the ability of students to finish their studies in the standard period of study, in addition, a questionnaire was used to collect the opinion of number of staff member in order to identify the most important causes of delay. The results of the study revealed that the capability process scale was 0.75, which is less than 1. This indicates that the inability of a large percentage of the graduates of the faculty of engineering at Misurata university to complete the undergraduate level on time. The results also showed that 64% of the graduates took a longer period than the standard period of study, while 24% of the graduates completed their studies within the standard period, the remaining percentage of graduates, which was only 12%, completed their studies less than the standard period. The results of the study further indicated that the most important causes of students’ delay in completing their undergraduate studies in the college of engineering were concentrated in three main causes, which are “students’ preoccupation with other work for the purpose of saving financial expenses” and “absence from lectures for a large percentage of students for various reasons” by 93%. for each of them, followed by the “low level of secondary education outcomes” with a rate of 86%.